The Charter and Code of the Ordinances of Yazoo City 174-75 (1908) - (:unkn) unknown (My University, 1906)
Ch. 20, § 300 : If any person, having or carrying any dirk, dirk knife, sword, sword-cane, or any deadly weapon, or other weapon the carrying of which concealed is prohibited, shall, in the presence of three or more persons, exhibit the same in a rude, angry, or threatening manner, not in necessary self-defense, or shall in any manner unlawfully use the same in any fight or quarrel, the person so offending, upon conviction thereof, shall be fined in any sum not less than seven dollars and fifty cents nor more than five hundred dollars, or be imprisoned not exceeding ninety days, or both. In prosecutions under this section, it shall not be necessary for the affidavit or indictment to aver, nor for the city to prove on the trial, that any gun, pistol, or other firearm was charged, loaded, or in condition to be discharged."
Keywords: BRANDISHING; DUELING